Effect of Bearing Compliance on Thermo-hydrodynamic Lubrication of High Speed Misaligned Journal Bearing Lubricated with Bubbly Oil - Basim Ajeel Abass (Al-Khawarizmi Engineering Journal, 2015)
Abstract